FURIN gene variants (rs6224/rs4702) as potential markers of death and cardiovascular traits in severe COVID‐19. Issue 8 (12th April 2022) - Coto, Eliecer; Albaiceta, Guillermo M.; Amado‐Rodríguez, Laura; García‐Clemente, Marta; Cuesta‐Llavona, Elías; Vázquez‐Coto, Daniel; Alonso, Belén; Iglesias, Sara; Melón, Santiago; Alvarez‐Argüelles, Marta E.; Boga, José A.; Rojo‐Alba, Susana; et al.
Abstract: Furin is a protease that plays a key role in the infection cycle of SARS‐CoV‐2 by cleaving the viral proteins during the virus particle assembly. In addition, Furin regulates several physiological processes related to cardio‐metabolic traits. DNA variants in the FURIN gene are candidates to regulate the risk of developing these traits as well as the susceptibility to severe COVID‐19. We genotyped two functional FURIN variants (rs6224/rs4702) in 428 COVID‐19 patients in the intensive care unit. The association with death ( N = 106) and hypertension, diabetes, and hyperlipidaemia was statistically evaluated. The risk of death was associated with age, hypertension, and hypercholesterolemia. The two FURIN alleles linked to higher expression (rs6224 T and rs4702 A) were significantly increased in the death cases (odds ratio= 1.40 and 1.43). Homozygosis for the two high expression genotypes (rs6224 TT and rs4702 AA) and for the T‐A haplotype was associated with an increased risk of hypercholesterolemia. In the multiple logistic regression both, hypercholesterolemia and the TT + AA genotype were significantly associated with death. In conclusion, besides its association with hypercholesterolemia, FURIN variants might be independent risk factors for the risk of death among COVID‐19 patients. Highlights: Furin plays an important role in the life‐cycle of SARS‐CoV‐2 Furin activity might regulate the risk for cardiovascular traits, such as hypertension and hypercholesterolemia. Two functional FURIN variants were associated with the risk of death among critical COVID‐19 patients. The observed association with mortality was independent of higher cholesterol levels. FURIN gene variants might be predictors of COVID‐19 severity and mortaility.